Scientific research as an instrument that empowers lifelong learning. case study with applied psychological students, political science, and public administration students - Hysa, Ferit; Ibraj, Bajram (Edelweiss Applied Science and Technology, 2024)
This study is related to the field of education. Acquisition of knowledge and skills has an important role in this education, but their renewal is just as important. Of particular importance is obtaining reliable, true knowledge. This study aims to identify the key tools that make it possible to facilitate and empower learning in higher education and create an indispensable culture for lifelong learning. The training of the student in the methodology, methods and practices of scientific research affects his empowerment in his professional training, updating and generating new knowledge throughout life as well as his motivation to solve life problems and his influence for a better company.